L. S. Sargsyan - Sargsyan , L. S. (Modern Psychology, 2025)
The article discusses the results of the research of Armenian young adults’ motives of consumer behavior. The process of developing a questionnaire for identifying consumer motives is presented. The peculiarities of consumer motives’ expression among young people are analyzed and interpreted. According to the study, the consumer behavior of young adults is primarily directed by internally oriented motives. Though, in consumption situations externally oriented motives are less involved in the behavior.
Keywords: consumer behavior, motive, consumption motives.